Time and space discretized nonlinear optimal control of freeway traffic flows - (:unkn) unknown (IFAC Secretariat, 2003)
Various linear and nonlinear control techniques available for lumped parameter systems can be adapted to the freeway traffic flow process by space discretized models. Id any case, it is important to analyze the control laws designed by vising different paradigms so that they can be compared for their effectiveness. Such a control model has been proposed in this study. It is based on the feedback linearization technique. In the proposed model, the macroscopic densities of the main-link segments (discrete space units) used in the feedback linearization technique are modified due to the direction of the shock waves between the contiguous segments. To reach this aim, the macroscopic flow and density parameters of the discrete space units are calculated at the end of each discrete time period, by using the cumulative occupancy and vehicle count measurements obtained from the traffic detectors. Simulation based comparisons studied in VISSIM are shown that the effectiveness of the feedback linearization technique can be increased by this way. The test results are satisfied. Copyright © 2003 IFAC.
Keywords: Freeway traffic control; Nonlinear optimal control; Ramp metering